1999
DOI: 10.1557/jmr.1999.0333
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of Ln(Mg1/2Ti1/2)O3 as substrates for high-Tc superconductor thin films

Abstract: Ln(Mg1/2Ti1/2)O3 (Ln = Dy, La, Nd, Pr, Sm, Y) compositions have been prepared, and their pertinent properties for use as thin film substrates for YBa2Cu3Ox (YBCO) were measured. X-ray diffraction shows that Ln(Mg1/2Ti1/2)O3 compositions have noncubic symmetry and the GdFeO3-type structure. Dielectric constant measurements revealed values between 22 and 27, which are larger than those of the LnAlO3 family. Quality factor (=1/ tan δ) of the ceramic specimens measured at room temperature was larger than 3000 at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 15 publications
0
78
0
Order By: Relevance
“…XRD analysis of the dielectric ceramics and electrode powder mixture sintered at the desired temperature is considered an acceptable way to analyze the interface reaction [15]. This method is widely used for the investigation of any reaction between dielectrics and electrode materials used in multilayer chip capacitors.…”
Section: Resultsmentioning
confidence: 99%
“…XRD analysis of the dielectric ceramics and electrode powder mixture sintered at the desired temperature is considered an acceptable way to analyze the interface reaction [15]. This method is widely used for the investigation of any reaction between dielectrics and electrode materials used in multilayer chip capacitors.…”
Section: Resultsmentioning
confidence: 99%
“…(Qf=59000GHz) (Cho et al 1997). For Nd(Mg 0.5 Ti 0.5 )O 3 , the corresponding value is 26, -49 ppmK -1 and 36900GHz, respectively (Cho et al 1999). XRD analysis showed that they can form solid solution with Ba 0.6 Sr 0.4 TiO 3 (Fig.…”
Section: Ferroelectric-dielectric Solid Solutionmentioning
confidence: 96%
“…Among them, Sm(Mg 0.5 Ti 0.5 )O 3 has a moderate dielectric constant (e r * 25), a high quality factor (Q 9 f * 65,500 GHz) and a negative temperature coefficient of resonance frequency (s f * -26 ppm/°C) [11], which limits its practical applications. In order to compensate the s f of Sm(Mg 0.5 Ti 0.5 )O 3 , CaTiO 3 was added to form (1 -x)CaTiO 3 -xSm(Mg 0.5 Ti 0.5 )O 3 solid solution, but that compound did not show ideal dielectric properties because of phase transformation [12].…”
Section: Introductionmentioning
confidence: 99%